NEW HOPE ON DRUG LEADS DEVELOPMENT FROM DEEP OCEAN: HALOGENATED ALKALOIDS OF AGELAS SPONGES - Hertiani, Triana (INDONESIAN JOURNAL OF PHARMACY, 2014)
Agelas sponge is found in abundancy from Indonesiaâs ocean. This sponge produces an important chemotaxonomic group of compounds, derived from pyrrole-imidazole alkaloids. This group of compounds is one of those exclusively found from marine environment. Marine sponges are reported to be promising drug lead producers having unique chemical structures of which many have no terrestrial counterparts. The objective of this report is to give an overview of the reported attempts from up to down stream to develop pyrrole-imidazole alkaloids as new drug lead. Literatures up to 2013 reporting this group of compounds from Agelas sponges were studied. Discussion on the halogenated alkaloids covers the producers, description of high chemical diversity, identification, biosynthesis and ecological relevance as well as their role as a promising drug candidate. Alternatives to provide continous supplies for drug development are also discussed considering that wild harvesting of the sponge producers can lead to ecological damage in the future . Broad range of interesting pharmacological importance as well as several success in developing synthetic route for production supports its development as drug candidate.Â